Revisiting Green Marketing Implementation in Halal Cosmetic Brands - Ika Diyah Candra Arifah (al-Uqud : Journal of Islamic Economics, 2020)
The growing green consumer who selecting products that socially and environmentally ethical products, encourages cosmetics producers in Indonesia to produce more environmentally friendly product in terms of materials, ingredients, packaging, and even the strategy to promote it. As this market segment continues to grow and develop, cosmetics manufacturers are required to be more competitive by applying green marketing values. Therefore, this study aims to investigate how halal cosmetic brands applying green marketing based on the concept of green marketing strategy and Islamic Marketing Ethics (IME). This case study uses a qualitative research approach that selecting four top halal cosmetic brands that marketed in Indonesia. Data was analyzed by data triangulation and method triangulation approach and presented in inductive summary. The results of the study concluded that among the top four halal cosmetics brands studied, two brands had implemented the concept of green marketing strategy and implementation comprehensively (shaded green and extreme green), while the other two brands applied lean green and defensive marketing strategy and implementation. The implication of this research is to provide suggestion to managerial marketing about how to create a more captivating halal products for all customers. The novelty of research proposes how is the level of Indonesian halal cosmetic brands green strategy that applying Islamic Marketing Ethics (IME).